Comparisons of factors correlated with successful smoking cessation between middle-aged and older smokers - Ya-Hui Chang; Jia-Ling Wu; Shang-Chi Lee; Chuan-Yu Chen; Chin-Wei Kuo; Esther Ching-Lan Lin; Shu-Ying Lo; Yu-Ying Huang; Chao-Ying Tsai; Pei-Hsing Hsieh; Chung-Yi Li (PLoS ONE, 2026)
Background As the elderly population expands, smoking cessation becomes increasingly vital due to their heightened risk of adverse health effects. This study investigated the factors influencing successful smoking cessation among older smokers (≥65 years) in Taiwan, comparing them with those in middle-aged smokers (40–64 years). Methods We conducted a retrospective cohort study involving participants aged 40 and above who engaged in smoking cessation therapies in Taiwan from 2012 to 2022. The primary outcome was self-reported smoking status six months post-treatment. Using logistic regression with generalized estimation equations, we calculated the adjusted odds ratios for successful cessation, considering various individual and ecological factors. Results Among 263,641 middle-aged patients (442,133 treatment sessions) and 42,650 older smokers (67,372 treatment sessions), cessation success rates were 39.59% and 45.22%, respectively. Overall, both groups shared similar factors influencing cessation success. However, shorter smoking duration was more strongly associated with quitting among older smokers (adjusted odds ratio, aOR=1.35; 95% CI = 1.22–1.50), whereas varenicline (aOR=1.33; 95% CI = 1.26–1.40), bupropion (aOR=1.24; 95% CI = 1.19–1.30), and higher urbanization (aOR=1.29; 95% CI = 1.26–1.33) had greater effects among middle-aged smokers. Conclusions While the underlying mechanisms of smoking cessation were similar across age groups, the relative influence of smoking duration, medication counseling, and institutional urbanization differed. These findings highlight the need for tailored interventions within the Tobacco Cessation Program, focusing on medication adherence and continuous counseling for middle-aged smokers, and improving accessibility and health management support for older adults.